Inklusi Keuangan dan Kinerja Usaha pada Usaha Mikro Kecil Menengah - Jevi Bela Pitaloka; Teguh Erawati (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2023)
This study aims to examine the effect of entrepreneurial knowledge, innovation, use of social media, and financial inclusion on business performance in Micro, Small and Medium Enterprises or MSMEs in Bantul Regency. The method used is quantitative with primary data sources. The population of this research is MSME actors in Bantul Regency and a sample of 109 respondents is obtained. The sampling technique used was convenience sampling. Data was collected by distributing questionnaires in the form of a google form link. This study uses a multiple linear regression model with the IBM SPSS version 20 program tool. The results show that entrepreneurial knowledge does not have a positive effect on business performance in MSMEs in Bantul Regency. Meanwhile, innovation, use of social media, and financial inclusion have a positive effect on business performance of MSMEs in Bantul Regency. Then seen from the results of the coefficient of determination (R²) of 0.444 or 44.4%, it can be concluded that entrepreneurial knowledge, innovation, use of social media, and financial inclusion can simultaneously affect business performance by 44.4% while the remaining 55.6% influenced by other factors outside this model.